Studies on Plasmodium Knowlesi Infections in Malaysian Borneo - Lee, Kim Sung (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This study aimed to identify and characterise the infections identified by microscopy as P. malariae in the Kapit division and to describe the morphology, clinical features and the epidemiology of the infections in Malaysian Borneo. In this study, eight randomly selected isolates, identified by microscopy as P. malariae, were characterised at the molecular level by cloning and sequencing of the small subunit ribosomal RNA (SSU rRNA) and the circumsporozoite protein (csp) genes.